The natural history of an arctic oil field : development and the biota - Truett, Joe C. (Joe Clyde), 1941-; Johnson, Stephen R., 1943- (Academic Press, 2000)
In spite of the harsh conditions that characterize the Arctic, it is a surprisingly fragile ecosystem. The exploration for oil in the Arctic over the past 30 years has had profound effects on the plants and animals that inhabit this frozen clime. The Natural History of an Arctic Oil Field synthesizes decades of research on these myriad impacts. Specialists with years of field experience have contributed to this volume to create the first widely available synopsis of the ecology and wildlife biology of animals and plants living in close association with an actively producing oil field.